2008
DOI: 10.2152/jmi.55.54
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine phosphorylase and dihydropyrimidine dehydrogenase are predictive factors of therapeutic efficacy of capecitabine monotherapy for breast cancer-preliminary results

Abstract: Capecitabine monotherapy was administered for 25 patients with advanced or recurrent breast cancer, and the clinical therapeutic efficacy and its relationship to expression of 5-fluorouracil-related enzymes (i. e., thymidine phosphorylase (TP), thymidylate synthase (TS) and dihydropyrimidine dehydrogenase (DPD)) were investigated. The expressions of TP, TS and DPD were determined by immunohistochemical staining techniques and rated using a scoring system of 1~4. The expression score for TP/DPD showed a statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
1
15
0
1
Order By: Relevance
“…In contrast, UFT (an oral fluoropyrimidine combining tegafur and uracil) showed no anti-tumor activity in the majority of 5-FU-resistant cell lines. Susceptibility of xenograft models to capecitabine correlates with the ratio of tumoral thymidine phosphorylase to dihydropyrimidine dehydrogenase [17,18], but such a correlation is not seen with UFT [17]. Therefore, it is possible that the activity of capecitabine in 5-FU-resistant tumors may relate to generation of 5-FU preferentially in tumor tissue, where thymidine phosphorylase concentrations are significantly higher than in non-tumor tissue [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, UFT (an oral fluoropyrimidine combining tegafur and uracil) showed no anti-tumor activity in the majority of 5-FU-resistant cell lines. Susceptibility of xenograft models to capecitabine correlates with the ratio of tumoral thymidine phosphorylase to dihydropyrimidine dehydrogenase [17,18], but such a correlation is not seen with UFT [17]. Therefore, it is possible that the activity of capecitabine in 5-FU-resistant tumors may relate to generation of 5-FU preferentially in tumor tissue, where thymidine phosphorylase concentrations are significantly higher than in non-tumor tissue [18].…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility of xenograft models to capecitabine correlates with the ratio of tumoral thymidine phosphorylase to dihydropyrimidine dehydrogenase [17,18], but such a correlation is not seen with UFT [17]. Therefore, it is possible that the activity of capecitabine in 5-FU-resistant tumors may relate to generation of 5-FU preferentially in tumor tissue, where thymidine phosphorylase concentrations are significantly higher than in non-tumor tissue [18]. Of note, in the clinical setting others have reported activity of capecitabine in patients previously exposed to 5-FU [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical studies on gastrointestinal and other cancers that have been largely treated with 5-FU-based chemotherapy have demonstrated that variation of expression of intratumoral enzymes involved in the metabolism of 5-FU and its derivatives (such as TS, DPD, and OPRT) is associated with efficacy and/or patient prognosis [21,[25][26][27][28][29]. However, only a few reports have demonstrated a relationship between TS, DPD, and OPRT expression and the outcome of pancreatic carcinoma patients treated with fluoropyrimidines [22,30,31], and no reports about such associations in pancreatic carcinoma patients treated with S-1 after surgical resection have been published.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, patients developing HFS during capecitabine therapy showed a trend towards increased intratumoral concentrations of TP and reduced intratumoral concentrations of dihydropyrimidine dehydrogenase (DPD) (and thus an increased TP-to-DPD ratio) compared with patients who did not experience HFS [23]. TP-to-DPD ratio also correlates with capecitabine efficacy [24]. Therefore, the apparent correlation between clinical efficacy and HFS may result from the relationship of both of these outcomes with the TP-to-DPD ratio.…”
Section: Discussionmentioning
confidence: 99%